Efficiency in Municipal Solid Waste Management: A Bibliometric Review of the Last 20 Years - Silva , Nájila Sena da; Sano , Edson Eyji; Chaves , Joselisa Maria (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The generation of solid waste represents a global challenge, as the complexity of materials and the methods used for disposal, such as landfills and incineration, do not ensure reduction at the source and contribute to greenhouse gas emissions. It is essential that countries adopt solid waste management assessment systems to monitor services, establish goals, and develop appropriate projects that ensure environmental quality. This study proposes to investigate the scientific literature to identify methods of solid waste management assessment used across different countries. The objective of this research is to map the main trends in scientific publications on the assessment of urban solid waste management. A bibliographic search was conducted using the Scopus database, and bibliometric analysis was applied to track the scientific evolution of articles on the subject. Graphic tools, including the R Bibliometrix package and VosViewer software, were used to generate network maps. The results highlight China as the most productive country in terms of publications and citations. The Waste Management journal featured the largest number of articles on this topic, and the most influential authors were Bovea MD, Medeiros GA, and Mancini SD. Word networks revealed the evolution of research topics over the decades. Among the methods analyzed in 10% of the articles, the Life Cycle Assessment (LCA) methodology was predominant. Within this framework, recycling and composting were identified as the most environmentally suitable scenarios for use in municipal management systems.